The Pittsburgh Sleep Quality Index: validity and factor structure in young people. - De la Vega, Rocío; Tomé-Pires, Catarina; Solé, Ester; Racine, Mélanie; Castarlenas, Elena; Jensen, Mark P.; Miró, Jordi (American Psychological Association, 2015)
The Pittsburgh Sleep Quality Index (PSQI) is a widely used measure of sleep quality in adolescents, but information regarding its psychometric strengths and weaknesses in this population is limited. In particular, questions remain regarding whether it measures one or two sleep quality domains. The aims of the present study were to (a) adapt the PSQI for use in adolescents and young adults, and (b) evaluate the psychometric properties of the adapted measure in this population. The PSQI was slightly modified to make it more appropriate for use in youth populations and was translated into Spanish for administration to the sample population available to the study investigators. It was then administered with validity criterion measures to a community-based sample of Spanish adolescents and young adults (AYA) between 14 and 24 years old (N = 216). The results indicated that the questionnaire (AYA-PSQI-S) assesses a single factor. The total score evidenced good convergent and divergent validity and moderate reliability (Cronbach's alpha = .72). The AYA-PSQI-S demonstrates adequate psychometric properties for use in clinical trials involving adolescents and young adults. Additional research to further evaluate the reliability and validity of the measure for use in clinical settings is warranted.
Es la versión preprint. https://openpolicyfinder.jisc.ac.uk/id/publication/3503
Keywords: Sueño; Psicometría; Pittsburgh Sleep Quality Index (PSQI); Psychometric properties; Confirmatory factor analysis; Sleep quality; Assessment